The Three Roles of Assessment: Gatekeeping, Accountability, and Instructional Diagnosis - Nagy, Philip (Canadian Journal of Education/Revue canadienne de l'éducation, 2000)
External assessment began as an imposed activity to provide quality control for a process. This gatekeeping role has a norm-referenced focus. A second role, ensuring accountability, emerged to judge the quality of education, an activity that has remained essentially norm-referenced. A third role, instructional diagnosis, is a recent phenomenon driven by the need to improve education and to provide educational, not political, justification. Traced from a measurement perspective, two requirements must be met for external assessment to yield instructionally diagnostic information: a reconceptualization of reliability, and development of more detailed and facilitative mechanisms for test scoring and interpretation. L’évaluation externe peut jouer plusieurs rôles : un rôle de garde barrière com- portant une approche normative; un rôle relié au principe de redevabilité jugeant de la qualité de l’éducation en termes politiques; un rôle de diagnostic pédagogique répondant au besoin d’améliorer l’éducation du point de vue de l’apprenant. Dans chacun de ces cas, deux exigences doivent être remplies pour que l’évaluation externe fournisse de l’information diagnostique sur le plan pédagogique : une reconceptualisation de la notion de fiabilité et l’élaboration de mécanismes plus détaillés et utiles pour la correction des tests et l’interprétation des résultats.